First observations on captive hatching and incubation period of the yellow‐nose skate Dipturus chilensis (Rajiformes: Rajidae), from the South‐Eastern Pacific Ocean. Issue 4 (30th August 2018) - Concha, Francisco; Morales, Naití; Hernández, Sebastián
Abstract : Twelve egg capsules laid in captivity by three females of Dipturus chilensis were incubated in the laboratory. After 252 ± 9.4 days, 10 skates successfully hatched, with a mean total length, disc length, and disc width of 17.2, 7.4, and 11.4 cm, respectively. This is the first report of captive hatching of D. chilensis and its corresponding incubation period.